(untitled) (LACCEI, 2024)
The objective of this research work was to design a supply management model for operating costs in an infrastructure company. The methodology has a mixed approach, non-experimental, cross-sectional design and a sample of 4 products. The techniques and instruments were: Observation (Observation Guide), Interview (Interview Guide) and Documentary Analysis (Summary Sheet), determining the validity and reliability, the judgment of experts in the logistic area was taken. Eight out of 20 root causes were prioritized: Delays in the delivery of suppliers, lack of follow-up of purchase orders, lack of purchasing policies, lack of purchasing planning, low purchasing budget, lack of personnel training, representing 57.29% of cost impact. Likewise, the improvements would be: ABC Method, Kraljic Matrix, Purchasing Procedure, Purchasing Operational Policies, Purchasing Budget, Approval and Evaluation of Suppliers, Training Plan minimizing cost overruns up to 60%. Finally, the company will eliminate profitability, reduce costs, with an investment of S/21,794.80.